2012
DOI: 10.4103/0019-5545.104822
|View full text |Cite
|
Sign up to set email alerts
|

Psychological morbidity among female commercial sex workers with alcohol and drug abuse

Abstract: Introduction:Substance abuse may act as precursors and also can form outcomes of sexual behaviors. The confluence of drug use, mental stressors, poverty, sexually transmitted diseases, low self-esteem and high-risk partners forms a fertile ground for psychological morbidity.Aim:To assess the psychological morbidity among female commercial sex workers (CSWs) who use alcohol and other substance abuse.Materials and Methods:One hundred consecutive CSWs with alcohol and drug abuse patients attending the psychiatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 12 publications
2
28
1
Order By: Relevance
“…The current study's finding of anxiety level of 61% among FEWs is much higher than found (a) among the Cambodian general population (16.7%, [35]) (b) among sex worker samples in Miami (37.4%; [36]) and (c) compared to sex worker in India (42%; [38]). This is likely due to high levels of risk and stress associated with Cambodian FEWs' lives.…”
Section: Discussioncontrasting
confidence: 72%
“…The current study's finding of anxiety level of 61% among FEWs is much higher than found (a) among the Cambodian general population (16.7%, [35]) (b) among sex worker samples in Miami (37.4%; [36]) and (c) compared to sex worker in India (42%; [38]). This is likely due to high levels of risk and stress associated with Cambodian FEWs' lives.…”
Section: Discussioncontrasting
confidence: 72%
“…() noted that 19% had reported a suicide attempt in the past 3 months. Furthermore, in Bangalore, India, among 100 female sex workers accessing a central hospital, 71% reported depression, 73% reported social dysfunction, and 42% reported anxiety (Pandiyan, Chandrasekhar, & Madhusudhan, ). In the one previous study on the mental health needs of sex workers in rural areas of the country, Hennick and Cunningham () reported that 92% of their sample endorsed clinical depression and 57% reported a past instance of a suicide attempt.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all the studies have been conducted among male subjects with the exception of few that have been conducted among female subjects[ 41 ] or have included female subjects. [ 19 20 ] Most of the studies have been conducted among individuals seeking treatment.…”
Section: Resultsmentioning
confidence: 99%